Effect of Intravenous Lipid Emulsion on Clozapine Acute Toxicity in Rats - Bahareh Sadat Yousefsani; Seyed Ahmad Mohajeri; Mohammad Moshiri; Amir Hossein Jafarian; Hossein Hosseinzadeh (Korean Pharmacopuncture Institute, 2019)
Objectives: Many studies have been reported the efficacy of intravenous lipid emulsion (ILE) as an antidote on acute lipophilic drug toxicity. Clozapine, highly lipophilic dibenzodiazepine neuroleptics, is an important medication in the schizophrenia therapy regimen. Acute intoxication with antipsychotics is one of the main reasons for the referral of poisoned patients to the hospital. We expected that ILE could be used for the therapy of acute clozapine intoxicated patients. Methods: We used two groups of consisting of six male rats. Both groups received a toxic dose of clozapine (40 mg/kg) intravenously, via the tail vein. After 15 minutes, they were treated with intravenous infusion of 18.6 mg/ kg normal saline (NS group), or 18.6 mg/kg ILE 20% (ILE group). We evaluated blood pressure (BP) and heart rate by power lab apparatus through the tail artery, ataxia by a rat rotary circle, seizure scores and death in multiple times after starting clozapine administration. For biochemical and pathological evaluations the samples of tissue and blood were taken. Results: Our results demonstrated that ILE 20% could return hypotension-induced clozapine better than normal saline. Furthermore, ataxia and seizure have rectified more rapidly and deaths reduced. Clozapine administration causes pancreatitis and lung injury but fat emulsion did not show an optimal effect on tissue damages caused by clozapine toxicity. Conclusion: In conclusion, ILE can remove toxic signs of clozapine same as other lipophilic medicines, however, clinical uses of ILE for this intention requires more appraisement to determine the precise implication and safety.